Dalla parte delle vittime: giustizia e prevenzione. Il caso di Sara Di Pietrantonio - Pelletti, Barbara; Iasonna, Stefania (Il sogno della farfalla, 2020)
This article deals with the lawsuit of a young woman killed by her ex-partner by analysing the courts record’s process. This case has been a turning point in the Italian jurisdiction with regards to gender based violence. The reason lies in the explicit recognition of stalking psychological violence as matrix of homicidal ideation. The objective of the authors is to highlight the symbolic and therefore preventive value of these judgements which identify in abuse and patriarchal domination experienced by the woman before the murder, a specific feature of feminicide. Cultural change, widely considered as fundamental in order to fight violence against women, can be promoted through the universal language of law which does not only condemn the single subject but the mentality embodied by the offender itself. This mentality is represented by a millenary patriarchal culture that our same legislation has being supporting until recently. Another fundamental aspect is the recognition of the objective psychological damage caused by the stalker to the victim. This is a wound which consequently impairs women’s capability to react. In order to achieve an effective prevention is necessary to raise awareness about the deep dynamics of sick relationships. This would allow to acknowledge the invisible violence hidden behind relationships lacking in affection: the negation and annulment pulsion theorised by Massimo Fagioli.